2017
DOI: 10.1038/tp.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of BDNF, BDNF pro-peptide and their precursor proBDNF in brain and liver tissues from psychiatric disorders: rethinking the brain–liver axis

Abstract: Brain-derived neurotrophic factor (BDNF) has a role in the pathophysiology of psychiatric disorders. The precursor proBDNF is converted to mature BDNF and BDNF pro-peptide, the N-terminal fragment of proBDNF; however, the precise function of these proteins in psychiatric disorders is unknown. We sought to determine whether expression of these proteins is altered in the brain and peripheral tissues from patients with psychiatric disorders. We measured protein expression of proBDNF, mature BDNF and BDNF pro-pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 48 publications
0
86
0
Order By: Relevance
“…In addition, we also found both SNI rats with or without anhedonia-like phenotypes have lower tissue levels of BDNF in the muscle and liver compared with those in sham-operated rats. Interestingly, we observed alterations in BDNF-TrkB signaling in the liver from mood disorders including major depressive disorder and bipolar disorder, suggesting a possible role of BDNF-TrkB signaling in mood disorders [47]. Given the key role of BDNF-TrkB signaling in psychiatric disorders [48,49], it is likely that alterations in BDNF-TrkB signaling may contribute to anhedonia susceptibility to SNI surgery.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, we also found both SNI rats with or without anhedonia-like phenotypes have lower tissue levels of BDNF in the muscle and liver compared with those in sham-operated rats. Interestingly, we observed alterations in BDNF-TrkB signaling in the liver from mood disorders including major depressive disorder and bipolar disorder, suggesting a possible role of BDNF-TrkB signaling in mood disorders [47]. Given the key role of BDNF-TrkB signaling in psychiatric disorders [48,49], it is likely that alterations in BDNF-TrkB signaling may contribute to anhedonia susceptibility to SNI surgery.…”
Section: Discussionmentioning
confidence: 78%
“…The participants were sorted Brain-derived neurotrophic factor (BDNF), the most abundant neurotrophin in the central nervous system (CNS), plays an important role in neurogenesis, neuronal survival, and synaptic plasticity [5,6]. BDNF levels measures in blood could reflect illness activity in the brain due to a positive correlation of BDNF levels between blood and cortex in mice, rats and pigs [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tropomyosin receptor kinase (TrkB), a receptor of BDNF on cell membrane, is involved in bipolar disorder [8,9]. Several studies have adopted the BDNF as a molecular candidate for developing bipolar disorder [6,10]. Recent studies had demonstrated that BDNF levels are lower in patients during active phases than BDNF levels in healthy controls [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In this context, Kingston and colleagues 26 and antipsychotic drug action. 30,31 In conclusion, we hope that this Special Issue illuminates (i) important aspects of evolving concepts of schizophrenia, schizoaffective disorder, bipolar disorder, and major depressive disorder with psychotic features, and (ii) how these aspects are increasingly complemented by yet more heuristic emerging concepts of psychotic ideation, psychotic illness, and pathobiology across conventional diagnostic boundaries within a milieu of psychosis. Such juxtaposition refreshes the field and increases the likelihood of progress.…”
mentioning
confidence: 93%
“…Liu and colleagues investigate the effects of Hcyb1, a novel inhibitor of phosphodiesterase2A (PDE2A), in 2 contexts: as a putative antidepressant agent and as a neuroprotective agent in terms of increasing cell viability/promoting neuronal proliferation. They report Hcyb1 to exert both antidepressant‐like effects in behavioral models and neuroprotective effects in cell lines that are likely mediated by cAMP/cGMP‐CREB‐BDNF signaling, disruption of which has been implicated both in depression and psychosis and in antidepressant and antipsychotic drug action …”
mentioning
confidence: 99%